2016
DOI: 10.1021/acs.jpcc.6b03011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrochemical Evaluation of Multivalent Vanadium Hydride Gels for Lithium and Hydrogen Storage

Abstract: ABSTRACT:A vanadium aryl hydride gel was prepared by thermal decomposition and subsequent hydrogenation of tetraphenyl vanadium and evaluated for electrochemical and hydrogen storage performance. Characterization by IR, XRD, XPS, nitrogen adsorption, and TGA suggests that the material consists predominantly of a mixture of vanadium centers in oxidation states of II-IV bound together by bridging hydride and phenyl groups. Electrochemical properties were explored to probe the reversible oxidation state behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…3D) are endothermic and do not increase or decrease significantly with increased surface coverage. This supports the mechanism discussed at length previously and supported by computations and high-pressure Raman measurements [15][16][17] in which the 20-40 kJ mol À1 H 2 energy expected for Kubas binding of hydrogen 8,9 is offset by twisting of the material as the pressure increases to open up new binding sites. 26 A MOF has been reported that undergoes structural deformation on application of pressure and this deformation influences the adsorption properties.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…3D) are endothermic and do not increase or decrease significantly with increased surface coverage. This supports the mechanism discussed at length previously and supported by computations and high-pressure Raman measurements [15][16][17] in which the 20-40 kJ mol À1 H 2 energy expected for Kubas binding of hydrogen 8,9 is offset by twisting of the material as the pressure increases to open up new binding sites. 26 A MOF has been reported that undergoes structural deformation on application of pressure and this deformation influences the adsorption properties.…”
Section: Resultssupporting
confidence: 87%
“…This method of synthesizing a solid-state transition metal hydride from a metal alkyl has been reported previously by our group for Ti, Cr, and V systems. [14][15][16][17] The resulting black air sensitive solid (KMH-1 as synthesized) still contained hydrocarbon as evidenced by the infrared (IR) spectrum ( Fig. S1, ESI †) and because of this was hydrogenated in the solid state at 373 K and 85 bar for 4 hours to give KMH-1 after 1st hydrogenation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years there has been an increasing interest in developing materials that exploit the Kubas interaction including, from our labs, those based on hydrazines 20 , hydrazides 21 , doped mesoporous silica molecular sieves 22,23 , and early transition metal alkyl hydride gels [24][25][26][27] . The latter have shown considerable promise as novel hydrogen storage materials;…”
Section: Introductionmentioning
confidence: 99%